Peran Kegunaan Informasi E-WOM Sebagai Variabel Mediasi Antara Anteseden Kegunaan Informasi E-WOM Terhadap Minat Beli Moisturizer Skintific di Shopee - Noor Hanna Vakhira; Saqofa Nabilah Aini (Universitas Warmadewa, 2025)
The development of digital technology has driven a transformation in Indonesian consumer behavior. Electronic word-of-mouth (E-WOM) has become one of the most popular marketing strategies today. Consumers tend to consider information available online before making a purchase. This study aims to examine the influence between the variables of opinion quality, source credibility, and information rating on buying interest in Skintific moisturizer mediated by the usefulness of E-WOM information at the Skintific Official Store at Shopee. This study uses quantitative research methods with a type of survey method. The number of samples in this study were 200 respondents obtained through purposive sampling technique. This study uses the Partial Least Square (PLS) approach which is a Structural Equation Model (SEM) equation model processed through SmartPLS 3.0 software. The results showed that source credibility had no significant effect on purchase intention, while the usefulness of E-WOM information had a significant effect on purchase intention.